2003
DOI: 10.1007/s00114-002-0398-8
|View full text |Cite
|
Sign up to set email alerts
|

Inverse correlation between mitochondrial size and metabolic competence: a quantitative cytochemical study of cytochrome oxidase activity

Abstract: Mitochondria are topologically closed bilayered systems where the synthesis of adenosine triphosphate (ATP) from adenosine diphosphate (ADP) and inorganic phosphate occurs via oxidative phosphorylation. The ordered architecture (and its extension) of the mitochondria (i.e. inner membrane, outer membrane and cristae) constitutes a critical topographic arrangement for their energy-providing mechanisms. Thus, quantitative estimations of the ultrastructural features of organelles preferentially stained by means of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
21
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 17 publications
3
21
1
Order By: Relevance
“…A recent report from our laboratory has clearly shown that the small and medium-sized organelles are much more efficient in providing adequate ATP amounts than are the organelles of larger size. 17,18 Considering our findings altogether, the present investigation confirms and strengthens the notion that mitochondria play a central role in regulating the processes involved in programmed cell death. In turn, this suggests that mitochondria may be considered reliable targets for intervention strategies in several pathological conditions (such as the neurodegenerative diseases typical of aging), for which cell death constitutes a well-documented step in the progression of the pathology, that is, Alzheimer's and Parkinson's disease.…”
Section: Discussionsupporting
confidence: 88%
“…A recent report from our laboratory has clearly shown that the small and medium-sized organelles are much more efficient in providing adequate ATP amounts than are the organelles of larger size. 17,18 Considering our findings altogether, the present investigation confirms and strengthens the notion that mitochondria play a central role in regulating the processes involved in programmed cell death. In turn, this suggests that mitochondria may be considered reliable targets for intervention strategies in several pathological conditions (such as the neurodegenerative diseases typical of aging), for which cell death constitutes a well-documented step in the progression of the pathology, that is, Alzheimer's and Parkinson's disease.…”
Section: Discussionsupporting
confidence: 88%
“…Although mitochondrial fragmentation reduces ATP production, enlarged mitochondria due to an imbalance favoring fusion over fission, produce more energy compared with normal mitochondria [11], [12]. However, the opposite has also been reported [13], [14].…”
Section: Introductionmentioning
confidence: 97%
“…COX activity was cytochemically evidenced as reported in our previous papers. [6][7][8] Briefly, the freshly excised tissue samples (40-60-μm thickness) were fixed 4-5 min in the following solution: 2.5% paraformaldehyde, 1.5% glutaraldehyde in 0.1 mol/L phosphate buffer, pH 7.4 + 4% sucrose. Following overnight rinse in the buffer sucrose solution, the samples were incubated for 4 h at 37 • C in the dark in the following solution (100 mL): 50 mg DAB, 27 mg cytochrome c, 4 g sucrose.…”
Section: Preferential Cytochemistry Of Cox Activitymentioning
confidence: 99%
“…Following overnight rinse in the buffer sucrose solution, the samples were incubated for 4 h at 37 • C in the dark in the following solution (100 mL): 50 mg DAB, 27 mg cytochrome c, 4 g sucrose. [6][7][8] Postfixation in osmium tetroxide was followed by embedding, sectioning, and contrasting procedures as for conventional electron microscopic procedures. According to the above-described procedure, in the DAB-COX reaction the dark precipitate from COX activity is markedly evident on the cristae and inner mitochondrial membrane and can be readily observed with the electron microscope.…”
Section: Preferential Cytochemistry Of Cox Activitymentioning
confidence: 99%
See 1 more Smart Citation